Plant breeding : a biometrical approach - Roy, Darbeshwar (Oxford, UK : Alpha Science International, 2012)
'Plant Breeding' starts with a description of traits and breeding systems including male sterility and self-incompatibility. It further describes the evolution of crop species, the breeding methods such as Pedigree, SSD, Bulk and Dihaploidy being employed in improving self-fertilising species
Includes bibliographical references and index
Keywords: Biometry; Plant breeding; Plant breeding -- Statistical methods